Fabrication of Microbicidal Silver Nanoparticles: Green Synthesis and Implications in the Containment of Bacterial Biofilm on Orthodontal Appliances - Farheen, Saba; Oanz, Abdul M; Khan, Nazoora; Umar, Mohd Saad; Jamal, Fauzia; Altaf, Ishrat; Kashif, Mohammad; Alshameri, Ansam Wadia; Somavarapu, Satyanarayana; Wani, Irfan Ahmad; Khan, Saba; Owais, Mohammad (Frontiers in Nanotechnology, 2022)
Among various metal-based nanoparticles, silver nanoparticles (AgNPs) manifest superior inhibitory effects against several microorganisms. In fact, the AgNP-based treatment has been reported to inhibit both sensitive and resistant isolates of bacteria and other disease-causing microbes with equal propensity. Keeping this fact into consideration, we executed bio-mediated synthesis of AgNPs employing extract of flower and various other parts (such as bud and leaf) of the Hibiscus rosa-sinensis plant. The physicochemical characterization of as-synthesized AgNPs was executed employing transmission electron microscopy (TEM), dynamic light scattering (DLS), zeta potential, Fourier transform infrared (FTIR) spectroscopy, and UV-Vis spectroscopy, etc. The as-synthesized AgNPs demonstrated strong antimicrobial activity against both Gram-positive and Gram-negative bacteria with equal propensity. The as-synthesized AgNPs successfully inhibited Streptococcus mutans (S. mutans), one of the main causative bacteria responsible for dental caries. Considering the fact that orthodontic appliances facilitate infliction of the oral cavity with a range of microbes including S. mutans, we determined the growth inhibitory and anti-adherence activities of AgNPs on orthodontic appliances. We performed microbiological assays employing AgNPs adsorbed onto the surface of nickel–titanium (Ni-Ti) orthodontic wires. A topographic analysis of the decontaminated Ni-Ti orthodontic wires was performed by scanning electron microscopy. In addition to antimicrobial and anti-biofilm activities against oral S. mutans, the as-fabricated AgNPs demonstrated significant inhibitory and anti-biofilm properties against other biofilm-forming bacteria such as Escherichia coli and Listeria monocytogenes.